Comparative genome analysis of 24 bovine-associated Staphylococcus isolates with special focus on the putative virulence genes - Åvall-Jääskeläinen, Silja (PeerJ, 2018)
Non-aureus staphylococci (NAS) are most commonly isolated from subclinical mastitis. Different NAS species may, however, have diverse effects on the inflammatory response in the udder. We determined the genome sequences of 20 staphylococcal isolates from clinical or subclinical bovine mastitis, belonging to the NAS species Staphylococcus agnetis, S. chromogenes, and S. simulans, and focused on the putative virulence factor genes present in the genomes. For comparison we used our previously published genome sequences of four S. aureus isolates from bovine mastitis. The pan-genome and core genomes of the non-aureus isolates were characterized. After that, putative virulence factor orthologues were searched in silico. We compared the presence of putative virulence factors in the NAS species and S. aureus and evaluated the potential association between bacterial genotype and type of mastitis (clinical vs. subclinical). The NAS isolates had much less virulence gene orthologues than the S. aureus isolates. One third of the virulence genes were detected only in S. aureus. About 100 virulence genes were present in all S. aureus isolates, compared to about 40 to 50 in each NAS isolate. S. simulans differed the most. Several of the virulence genes detected among NAS were harbored only by S. simulans, but it also lacked a number of genes present both in S. agnetis and S. chromogenes. The type of mastitis was not associated with any specific virulence gene profile. It seems that the virulence gene profiles or cumulative number of different virulence genes are not directly associated with the type of mastitis (clinical or subclinical), indicating that host derived factors such as the immune status play a pivotal role in the manifestation of mastitis.